MARKETING MANAGEMENT OF ENTERPRISE - Eugeniusz Michalski (Polityki Europejskie, Finanse i Marketing)
The main goal of this article is to present how the new conception of marketing mix affects delivering value to customers and benefit an enterprise. The task of marketing management is to make the good and service available when a customer is ready to buy it. An enterprise needs timely, accurate and relevant information on customers, competitors and new socio-economic trends in the country and the world. The analysis of marketing management paradigm and creation of value based management were carry out. Next, the concept of marketing strategy and SWOT analysis were under consideration. Lastly, the impact of information technology on marketing management were described.